Yahoo Answers: Answers and Comments for Mathematical induction problem...help? [Mathematics]
Copyright © Yahoo! Inc. All rights reserved.
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
From *dolly*
enUS
Tue, 31 Aug 2010 07:08:03 +0000
3
Yahoo Answers: Answers and Comments for Mathematical induction problem...help? [Mathematics]
292
38
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
https://s.yimg.com/zz/combo?images/emaillogous.png

From camara: you like 2 issues: a base case and an "in...
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
Mon, 03 Oct 2016 06:41:36 +0000
you like 2 issues: a base case and an "inductive bounce of religion". then you teach the two. in this actual occasion, your base case would be S(a million), and your "bounce of religion" would be that no count number if this is authentic for S(n), then it is likewise authentic for S(n+a million). S(a million) = a million^2 = a million * 2 * 3 / 6 = a million. Sp. authentic for S(n), teach for S(n + a million). purpose: teach that S(n+a million) = (n + a million)(n + 2)(2n + 3) / 6 = (n^2 + 3n + 2)(2n + 3) / 6 = (2n^3 + 9n^2 + 13n + 6) / 6 start up with the definition of S(n+a million): S(n+a million) = S(n) + (n+a million)^2 = S(n) + n^2 + 2n + a million and then exchange the equation for S(n), utilising the inductive hypothesis: S(n+a million) = n(n + a million)(2n + a million) / 6 + n^2 + 2n + a million = (2n^3 + 3n^2 + n) / 6 + n^2 + 2n + a million = ((2n^3 + 3n^2 + n) + (6n^2 + 12n + 6)) / 6 = (2n^3 + 9n^2 + 13n + 6) / 6 by skill of ways, you ought to be certain you already know this data, and then attempt to stick to it to a minimum of something else.

From Narendran: Let's take p(1); here, n = 1
LHS : 10^1 ...
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
Tue, 31 Aug 2010 07:28:10 +0000
Let's take p(1); here, n = 1
LHS : 10^1 + 3 x 4^(1+2) + 5
= 10 + 3 x 4^3 + 5
= 15 + 3 x 64
= 15 + 192
= 207
Now, if LHS is divisible by 9, remainder = 0
207 / 9 : Q = 23 and R = 0
Therefore, LHS = RHS and p(1) is true...
Now we assume that p(k) is true; here, k ∈ N
So, 10^k + 3 x 4^(k+2) + 5 is divisible by 9
=> 10^k + 3 x 4^(k+2) + 5 = 9m ; let m be any natural number...(it can vary)
=> 10^k = 9m  3 x 4^(k+2)  5 ; Subtract 3 x 4^(k+2) + 5 from both sides  (1)
Now, we've to prove that p(k+1) is true ; here k + 1 = n and k ∈ N
10^n + 3 x 4^(n+2) + 5
= 10^(k+1) + 3 x 4^(k+1+2) + 5{As we said that n = k+1}
= 10^k x 10 + 3 x 4^(k+3) + 5
= ( 9m  3 x 4^(k+2)  5)x10 + 3x4^(k+3) + 5 {We put 10^k from (1) here...}
= 9(10m)  3x10 x 4^(k+2)  50 + 3x4^(k+3) + 5
= 9(10m)  3x10x4^(k+2) + 3x4^(k+2)x4  45
= 9(10m)  3 x 4^(k+2)x(104 )  45 {Take 3 x 4^(k+2) common}
= 9(10m)  9(5)  18 x 4^(k+2) {as 45 = 9(5) }
= 9(10m)  9(5)  9(3x4^(k+2)) {as 18 = 9x3}
= 9(10m  5  3x4^(k+2)) {Take 9 common from all 3 terms...}
That's it... Let 10m  5  3^4(k+2) be any variable Natural number, p
=9p => It's divisible by 9...
Therefore, p(k+1) is true...
And by the Principle of Mathematical Induction, and for all true values of k, p(k+1) is true, p(n) is true. This means that the formula is proved!
Hope this helps...

From gôhpihán: Let P(n) be the predicate such that
10^n + 3(...
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
Tue, 31 Aug 2010 07:19:59 +0000
Let P(n) be the predicate such that
10^n + 3(4^(n + 2)) + 5 is divisible by 9
for all n ≥ 0
The basic step, prove that P(0) is true
10^0 + 3(4^(0 + 2)) + 5 = 54
9  54
so P(0) is true
Now assume P(k) is true
then
10^k + 3(4^(k + 2)) + 5 must be divisible by 5
Then we must prove that P(k + 1) is also true
P(k + 1)
= 10^(k + 1) + 3(4^(k + 3)) + 5
= (10^k)(10^1) + 3(4^(k + 2))(4^1) + 5
= 10(10^k) + 3(4^(k + 2))(4) + 5
= 9(10^k) + (10^k) + 12(4^(k + 2)) + 5
= 9(10^k) + (10^k) + 3(4^(k + 2)) + 9(4^(k + 2)) + 5
= [ 9(10^k) + 9(4^(k + 2)) ] + (10^k) + 3(4^(k + 2)) + 5
= 9 [ (10^k) + (4^(k + 2)) ] + [ (10^k) + 3(4^(k + 2)) + 5 ]
Since 9 [ (10^k) + (4^(k + 2)) ] is divisible by 9 as it has a factor of 9 when factorized, and we assumed P(k) is true or [ (10^k) + 3(4^(k + 2)) + 5 ] is divisible by 9
Both the terms in P(k + 1) is divisible 9, which makes P(k + 1) divisible by 9, thus P(k + 1) is valid
P(k) ==> P(k + 1)
Hence this concludes the proof.

From Como: This could be tricky.
It is even trickier if ...
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
Tue, 31 Aug 2010 07:13:18 +0000
This could be tricky.
It is even trickier if the presentation of the question is suspect.
More brackets required.

From ?: Mistake: it should be 10^n+3*4^(n+2)+5 not &qu...
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
Tue, 31 Aug 2010 08:08:41 +0000
Mistake: it should be 10^n+3*4^(n+2)+5 not "3.4^(n+2)".
Let p(n)="10^n+3*4^(n+2)+5 is divisible by 9".
p(1):10^4+3*4^3+5
=10197 is divisible by 9 (1+1+9+7=18)=>
p(1) is true.
Assume p(k) is true for k>=1, where k is an integer. Then
p(k+1):10^(k+1)+3*4^(k+2)+5
=10*10^k+3[(4^(k+1))*(3+1)]+5
=9*10^k+9*4^(k+1)+[10^k+3*4^(k+1)+5]
is divisible by 9 =>
p(k+1) is true too
So, p(n) is true for any +ve integer n.

From Anonymous: Mistake: it should be 10^n+3*4^(n+2)+5 not &qu...
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
https://answers.yahoo.com/question/index?qid=20100831070803AAUuVau
Tue, 31 Aug 2010 07:44:36 +0000
Mistake: it should be 10^n+3*4^(n+2)+5 not "3.4^(n+2)".
Let p(n)="10^n+3*4^(n+2)+5 is divisible by 9".
p(1):10^4+3*4^3+5
=10197 is divisible by 9 (1+1+9+7=18)=>
p(1) is true.
Assume p(k) is true for k>=1, where k is an integer. Then
p(k+1):10^(k+1)+3*4^(k+2)+5
=10*10^k+3[(4^(k+1))*(3+1)]+5
=9*10^k+9*4^(k+1)+[10^k+3*4^(k+1)+5]
is divisible by 9 =>
p(k+1) is true too
So, p(n) is true for any +ve integer n.